Solution of the neutron transport equation by the Method of Characteristics using a linear representation of the source within a mesh - Mazumdar, Tanay; Degweker, S.B. (Annals of nuclear energy, 2017)
•In Method of Characteristics, the neutron source within a mesh is expanded up to linear term.•This expansion reduces the number of meshes as compared to flat source assumption.•Poor representation of circular geometry with coarser meshes is corrected.•Few benchmark problems are solved to show the advantages of linear expansion of source.•The advantage of the present formalism is quite visible in problems with large flux gradient. A common assumption in the solution of the neutron transport equation by the Method of Characteristics (MOC) is that the source (or flux) is constant within a mesh. This assumption is adequate provided the meshes are small enough so that the spatial variation of flux within a mesh may be ignored. Whether a mesh is small enough or not depends upon the flux gradient across a mesh, which in turn depends on factors like the presence of strong absorbers, localized sources or vacuum boundaries. The flat flux assumption often requires a very large number of meshes for solving the neutron transport equation with acceptable accuracy as was observed in our earlier work on the subject. A significant reduction in the required number of meshes is attainable by using a higher order representation of the flux within a mesh. In this paper, we expand the source within a mesh up to first order (linear) terms, which permits the use of larger sized (and therefore fewer) meshes and thereby reduces the computation time without compromising the accuracy of calculation. Since the division of the geometry into meshes is through an automatic triangulation procedure using the Bowyer-Watson algorithm, representation of circular objects (cylindrical fuel rods) with coarse meshes is poorer and causes geometry related errors. A numerical recipe is presented to make a correction to the automatic triangulation process and thereby eliminate this source of error. A number of benchmark problems are analyzed to emphasize the advantage of the source expansion method and the need to correct the triangular representation of the geometry.